Pengembangan Usaha Produksi Olahan Tempe Di UMKM Keripik Tempe Mak Ribut Desa Loning Kecamatan Petarukan Kabupaten Pemalang - Arif Hadi Prasetyo; Tri Handayani; Rengga Kusuma Putra; Dian Karisma; Nunung Wulan Sari; Rofiqoh Abibah; Dewi Ratna Sari; Silva Maily Chintya (Pusat Riset dan Inovasi Nasional, 2025)
Mentoring activities for MSMEs engaged in snacks, namely tempeh chips. Production activities are carried out every day because of the many enthusiasts and consumers who like the products of the Mak Ribut Tempeh Chips MSME. The purpose of this activity is to The purpose of this activity is to provide assistance for business development in MSMEs by identifying problems that exist in MSMEs, and trying to provide alternative solutions. After conducting the observation stage, several problems were found faced by MSMEs, including not having a business profile, not having a logo, not having a promotional Banner, not having a packaging sticker, not having a stamp, not having promotional media in the form of product photos, production videos and promotional videos, not having a social media account, not knowing the calculation of HPP, and not having simple financial records. During the mentoring activities that created a series of activities that resulted in several programs and after analyzing the UMKM Keripik Tempe Mak Ribut produced a positive impact on UMKM owners such as having a business profile that is useful as a business identity, logo, Banner, packaging stickers that are useful for introducing product brands, stamps, product photos, production videos, promotional videos, social media accounts, as a promotional media in marketing their products, and updates on gmaps so that consumers know the location of the business. Calculation of HPP (Cost of Goods Sold) so that UMKM know how much profit is obtained, as well as simple bookkeeping so that business finances are organized and not mixed with personal finances.